2022
DOI: 10.3390/ijerph192013377
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 Perceived Risk on Internet Addiction among College Students in China: An Empirical Study Based on the Structural Equation Model

Abstract: This study focused on COVID-19 perceived risk and Internet addiction among Chinese college students during the lockdown. On the basis of the Social Cognitive Theory, this study proposed a mediating model to evaluate the mediating role of difficulties in regulating emotion between the COVID-19 perceived risk and Internet addiction. A questionnaire survey was conducted among 690 college students during the COVID-19 lockdown in China. The results showed that the COVID-19 perceived risk was significantly positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Encourage workplace teams to set clear work boundaries, incorporate rest periods, and avoid prolonged, uninterrupted online work sessions. Encourage family members to offer emotional support, spend quality time together, and foster open communication within the family unit [8].…”
Section: Interventions Based On Research Resultsmentioning
confidence: 99%
“…Encourage workplace teams to set clear work boundaries, incorporate rest periods, and avoid prolonged, uninterrupted online work sessions. Encourage family members to offer emotional support, spend quality time together, and foster open communication within the family unit [8].…”
Section: Interventions Based On Research Resultsmentioning
confidence: 99%
“…A mediation model to assess the mediating role of emotion regulation difficulties between perceived risk of COVID-19 and Internet addiction in 690 university students during the pandemic in China was used. They found that there is an internal influence of the perceived risk of COVID-19 on the Internet addiction [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, DER is frequently reported as a mediating factor in studies on adolescent health issues in various national cultures [57,[59][60][61]. In particular, Pan et al [61] discovered a significant mediating effect of DER between the perceived risk of COVID-19 epidemics and internet addiction among Chinese university students.…”
Section: Iu Der and Mhmentioning
confidence: 99%